Effects of actuator-substrate ratio on hydrodynamic and propulsion performances of underwater oscillating flexible structure actuated by macro fiber composites. (1st May 2022) - Lou, Junqiang; Gu, Ting; Chen, Tehuan; Yang, Yiling; Xu, Chao; Wei, Yanding; Cui, Yuguo
Graphical abstract: Highlights: Actuation effects on the hydrodynamic and propulsion performances of flexible fin. An optimal balance is achieved as the actuator-substrate ratio approaches 0.6. Underwater resonant frequency increases linearly with actuator-substrate ratio. Abstract: Oscillating flexible structures driven by smart actuators are promising thrust-producing components for underwater bionic vehicles. In this study, the hydrodynamic and propulsion performances of an oscillating flexible structure driven by macro fiber composites (MFCs) are investigated at varying actuator-substrate ratios. Numerical and experimental results demonstrate that the underwater resonant frequency increases approximately linearly with increasing actuator-substrate ratio. Moreover, the ratios of the in-air and underwater resonant frequencies vary with differing actuator-substrate ratios, and are mainly determined by the equivalent mass density. The effects of the actuator-substrate ratios on several characteristic parameters related to the propulsion performance are investigated and compared. The results suggest the generated mean thrust of the fully actuated case is the largest, but the power efficiency is the lowest among all the actuator-substrate ratios investigated, because this case has the lowest characteristic velocity and Reynolds number. In contrast, the highest power efficiency and lowest generated thrust are observed in the longest substrate case with the smallest actuator-substrate ratio. An optimal balance between the power efficiency and generated thrust is achieved when the actuator-substrate ratio approaches 0.6, in which case the characteristic parameters of propulsion performance are the highest among all the cases. These findings can provide useful guidelines for the design of efficient underwater bionic devices propelled by flexible fins driven by MFCs and other smart actuators.